Organization citizenship behavior in public sector / Nazia Marin and Rosni Abdul - Marin, Nazia; Abdul, Rosni (2013)
The Organization Citizenship Behavior (OCB) has brought important matter to the organization where it can ensure the loyalty of public servants toward their organization. The objectives of the study are to determine the level of Organization Citizenship Behavior (OCB) among the public servant and also to analyze the association between the factors and Organization Citizenship Behavior (OCB). The study demonstrates the association of the individual-factors of job satisfaction, job involvement, organization commitment and public service motivation with the level of Organization Citizenship Behavior possessed by civil servants of the public sector organization.